ABORSI DALAM PANDANGAN HUKUM ISLAM - Rofiq, Nur; Azizah, Nur; Firnanda, Irma; Haikal, M. Wisnu; Oktavian, Dida (Jurnal Al-Wasith : Jurnal Studi Hukum Islam, 2023)
Abortion is not just a medical or public health problem, but also a societal problem caused by the strong influence of western free ideology. Abortion is the act of ending a pregnancy by forcibly aborting or removing the fetus in a woman's womb. The act of abortion deprives a fetus of its right to life and also endangers the safety of the mother of the fetus. This article aims to understand the dangers and perspectives of abortion in Islamic law. This research uses literature methods obtained from various sources such as journals and articles. With the topic raised, namely the Practice of Abortion in Islamic Law, the author is interested in this topic to develop knowledge about Abortion in Islamic Law